Tests de comportement des sols salés ou non salés vis-à-vis de l'eau - Sigala F.; Fies J.C.; Guennelon R. (Reuse of low quality water for irrigation, 1989)
This paper presents useful tests for studying the stability of aggregates, clumps and clump-clusters, related to dispersive water action. Sodic aggregates are not as strong as non-sodic ones, but for both materials the resistance against breaking depends directly on the moisture content. The actual dispersivity (water dispersed particles smaller than 20 pm. compared to the effective sum 'clay +silt') is quite the same for both kinds of soils. The main differentiating desaggregation process is the shivering of aggregates. For clumps the quantity of shifted material (after fragmentation and dispersion by drops of water) is linearly dependent on the volume of water falling down to the sample; it depends on the actual state of the sample, i.e. humid or dry, and on the level of structural porosity. When little clumps are organised in rather thin beds, the impact of water drops leads to a compaction of the surface sheet, more important for sodic material, which results in pounding and a decrease in infiltration.
Aswan Seminar, 1988/01/16-21, Cairo (Egypt)